Kewenangan Notaris Dalam Penerapan Prinsip Mengenali Pemilik Manfaat Pada Perseroan Terbatas - Julyatmikha, I Komang Ferdyan; Widiatedja, I Gusti Ngurah Parikesit (Acta Comitas, 2025)
The purpose of this study is to examine the Notary's authority in implementing the principle of identifying the beneficial owner in a limited liability company, how the Notary's authority is exercised in disclosing the beneficial owner, and the Notary's responsibility for undisclosed beneficial owners in an authentic deed. The writing method used in this research is normative legal research with an approach based on laws and regulations. The results of this study indicate that Notaries have the authority to disclose the beneficial owners during the establishment, registration, and ratification of the corporation to ensure the validity of the authentic deed made by the Notary. The Notary's responsibility for the deed made, when a Beneficial Owner is found, is that, in principle, the Notary does not bear absolute responsibility if a beneficial owner is not disclosed by the company. However, of course, if based on all the data and information provided by the client, the Notary still fails to identify and verify the beneficial owner, the Notary could be held liable under Article 1365 of the Civil Code.  Kata Kunci: Kewenangan, Tanggung Jawab, Notaris, Pemilik Manfaat,